2013
DOI: 10.5194/bg-10-3007-2013
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration on an aging managed heathland: identifying an appropriate empirical model for predictive purposes

Abstract: Heathlands are cultural landscapes which are managed through cyclical cutting, burning or grazing practices. Understanding the carbon (C) fluxes from these ecosystems provides information on the optimal management cycle time to maximise C uptake and minimise C output. The interpretation of field data into annual C loss values requires the use of soil respiration models. These generally include model variables related to the underlying drivers of soil respiration, such as soil temperature, soil moisture and pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Possible mechanisms to explain this lag effect could be the Birch effect as described above, or the decomposition of roots that died during drought-induced senescence. Moreover, plants can allocate large but variable fractions of their photosynthates belowground (Vicca et al, 2012b), with potentially rapid and strong effects on the autotrophic component of SCE (Bahn et al, 2008;Högberg et al, 2001;Kuzyakov and Gavrichkova, 2010). Hence, the results from this experiment also emphasize the need to separate autotrophic from heterotrophic respiration to fully explore the exact mechanisms underlying SCE responses.…”
Section: Within-experiments Variability In Predictability Of Soil Co 2mentioning
confidence: 88%
See 1 more Smart Citation
“…Possible mechanisms to explain this lag effect could be the Birch effect as described above, or the decomposition of roots that died during drought-induced senescence. Moreover, plants can allocate large but variable fractions of their photosynthates belowground (Vicca et al, 2012b), with potentially rapid and strong effects on the autotrophic component of SCE (Bahn et al, 2008;Högberg et al, 2001;Kuzyakov and Gavrichkova, 2010). Hence, the results from this experiment also emphasize the need to separate autotrophic from heterotrophic respiration to fully explore the exact mechanisms underlying SCE responses.…”
Section: Within-experiments Variability In Predictability Of Soil Co 2mentioning
confidence: 88%
“…For this and further analyses, experiments with no more than 10 data points were discarded. The four models (which have been used previously, see, for example, Curiel Yuste et al, 2003;Kopittke et al, 2013) were log (SR) = a + bST + cSWC,…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Efforts have been made to develop diffusivity models for estimating R soil with the soil gradient method (Maier and Schack-Kirchner, 2014;Moldrup et al, 2001), but an empirical calibration with chamber measurements is still necessary (Figure 3, Issue 2.d) for reliable long-term R soil measurements (Roland et al, 2015;Sánchez-Cañete et al, 2017). In studies where non-steady state chambers are used, R soil is usually estimated from the rate of change of CO 2 concentrations in relation to time using linear or exponential models (Kopittke et al, 2013;Pihlatie et al, 2013). However, recent studies have shown the usefulness of hierarchical Bayesian models in order to improve R soil estimates (Ogle et al, 2016).…”
Section: Measurements Of R Soilmentioning
confidence: 99%
“…However, ER models based only on temperature often show a lack of fit to seasonal data due to confounding contributions from biomass dynamics and therefore some seasonal studies include cluster-wise ER modelling for distinct plant phenological stages to overcome such confounding effects (Beetz et al, 2013;Poyda et al, 2016). Another approach has been to use instantaneous GPP measured under ambient PAR as a biomass proxy (Larsen et al, 2007;Kopittke et al, 2013). However, GPP is strongly sensitive to PAR, and coupling ER with GPP therefore also makes ER sensitive to diel PAR fluctuations which may not be generally valid.…”
Section: Flux Modellingmentioning
confidence: 99%